EFFETS D’UNE TEMPERATURE FRAICHE ET D’UN APPORT EXOGENE DE REGULATEURS DE CROISSANCE SUR DES SEMIS DE CHENE LIEGE - Rached-Kanouni, Malika; Benmansour, Fayçal; Alatou, Djamel (European Scientific Journal, ESJ, 2013)
The seedlings of Cork oak (Quercus suber L.) cultivated in uniform conditions at 25Â°C for a duration of long day of 16 hours are transferred for a week to a cool temperature of 5Â°C, to precise morphological stages. After coming back to initial conditions of cultivation, the temporal and spatial modifications are observed on waves. When the seedlings are transferred to â€œfull bloom budâ€, the caulinair strength phase last more time, and the component â€œrest periodâ€ is abolished. Concerning the other stages of transfer â€œswollen bud and rest periodâ€, the duration of rest period and the formation of scales increase with the formation of semi-phase for the first stage. So, some spatio-temporel modifications appear, they are similar to those observed by the application of growthâ€™s regulators of type gibberelic acid at full-bloom bud stage and rest period and cytokinine (kinetic) at swollen stage.